PENGARUH PERMODALAN, KUALITAS KREDIT, LIKUIDITAS DAN EFFISIENSI TERHADAP PROFITABILITAS DAN KEBIJAKAN DIVIDEN SERTA IMPLIKASINYA TERHADAP KAPITALISASI PASAR BANK KBMI 4 - I Wayan Budi Artha; Ni Luh Sili Antari (Journal of Applied Management Studies, 2023)
The purpose of this study is to analyze and prove empirically the effect of capital, credit quality, liquidity and efficiency on profitability and dividend policy and their implications for market capitalization in bank groups based on core capital 4 (KBMI 4). The research period is 10 years 2013 – 2022, with the sampling technique being saturated sampling, that is, all members of the bank population included in KBMI 4 are used as samples. The results showed that the profitability of the KBMI 4 bank was influenced by credit quality, liquidity and efficiency, while the dividend policy was influenced by capital, asset quality and efficiency. Both profitability and dividend policy have a positive and significant effect on market capitalization. Profitability and dividend policy should be maintained and improved so that market capitalization growth increases and investor confidence is maintained.